Overview of hemodynamic status in patients under spinal anesthesia - Kabnani, Melinda Winarti; Susanto, Amin; Hikmanti, Arlyana (Journal of Midwifery and Nursing, 2025)
The purpose of this study was to evaluate the hemodynamic picture of patients receiving spinal anesthesia at RSUD Dr. Soedirman Kebumen, focusing on changes in blood pressure, pulse, and oxygen saturation before and after anesthetic injection. This study used quantitative method with descriptive design and cross-sectional approach. The results showed that before injection, 81.0% of patients had normal blood pressure, but after injection, there was an increase in hypotension cases to 17.0% at the 5th minute. By the 20th minute, 93.2% of patients had normal blood pressure again. For pulse, 10.9% of patients had tachycardia before injection, which increased to 6.8% at the 20th minute after injection. Oxygen saturation remained stable, with 100% of patients achieving normal saturation at the 5th and 20th minutes. The conclusion of this study shows that spinal anesthesia can cause significant hemodynamic changes, especially a decrease in blood pressure and an increase in tachycardia frequency, although oxygen saturation remained stable.